Pemberdayaan Masyarakat Kampung Germas Desa Pinggir: Pembuatan Taman Asman Toga Untuk Mendukung Kesehatan Keluarga - Haq, Rynda Naashehatul; Agus Darmawan; Aulia, Syifana (Universitas Negeri Semarang, 2025)
Community empowerment is a crucial aspect in efforts to improve health at the village level, especially through community-based initiatives. This community service focuses on the implementation of the